Double lives : spies and writers in the secret Soviet war of ideas against the West - Koch, Stephen 1941- (The Free Press, 1994)
"The goal was to turn the Russian revolution into a world revolution, and the strategy was a masterful campaign led by a propaganda genius to align Western intellectuals with Stalin's Soviet Union. The man assigned to this task by the Politburo was Willi Munzenberg, a German communist living in Paris, a publisher and brilliant manipulator of public opinion. He recruited the notable artists and writers of the age, some conscious of their role, others utterly unaware of their part in this carefully orchestrated crusade." "The full story of this clandestine army has never before been told, since most of the celebrities who led these double lives either did so in total secrecy, or were themselves unaware of who was really pulling the strings. Leading intellectuals, including Lillian Hellman, Andre Gide, Andre Malraux, Ernest Hemingway, Dorothy Parker, John Dos Passos, Bertolt Brecht, and many others, either were among Munzenberg's "agents of influence" or were manipulated by them. Most had enlisted in their idealism for the anti-Fascist movement (privately, Munzenberg used the term "Innocents' Clubs" for his various front organizations), yet not a few of these writers and artists soon found themselves defending the most debased Soviet actions and principles." "Steven Koch masterfully recounts this astounding story of betrayal, covert operations, and even murder, which played itself out on an international stage from secret trials in Moscow to the halls of M15 in London, to New York and Hollywood. From the early 1930s to the mid 1960s, there were few significant episodes between East and West in which Munzenberg's recruits, or their successors, did not play a dramatic and decisive role. Among many other stunning revelations, Koch discloses new insights into how the German and Soviet secret services collaborated in the 1930s so that Hitler and Stalin could destroy their domestic enemies, a juncture leading to Hitler's Blood Purge and Stalin's Great Terror."